EFFECT OF AN ALKYL CHAIN ADDITION TO METALLOPORPHYRINS ON BLUE LIGHT PHOTODYNAMIC INACTIVATION OF ESKAPE AND ATYPICAL PATHOGENS - (:unkn) unknown (My University, 2023)
The trending rise in antibiotic resistance poses an enormous public health threat. These antimicrobial-resistant infections not only create an economical burden on individuals and healthcare systems, but also lead to prolonged hospitalizations and mortality rate. Among those highly resistant bacteria are the ESKAPE pathogens, which defines a group of Gram-positive and -negative bacteria that has been associated with multidrug resistant nosocomial infections. They represent more than 40% of species isolated from bloodstream infections exhibiting increased resistance to empirical antimicrobial therapy, length of hospitalization, cost of clinical care, and mortality rate compared to non-ESKAPE pathogens. Therefore, an alternative treatment approach to antimicrobials is warranted. Photodynamic inactivation (PDI) is a potential alternative treatment against these pathogens. It relies on incubating the targeted bacteria with an excitable photosensitizer (PS) chemical agent in the presence of oxygen molecules and the microorganism. Then, utilizing visible light at an appropriate wavelength to transition PS molecules into an excited state creates reactive oxygen species (ROS) that ultimately damage bacterial cells. One of the more commonly studied PS molecules are tetra-cationic TMPyP porphyrin derivatives. Previously, we have shown that among multiple metalloporphyrin derivatives, PdT4 and ZnT4 had the strongest bactericidal effects against methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli using a portable 405 nm LED light. Here we aimed to determine the impact of adding C14 alkyl chain to PdT4 and ZnT4 on bacterial binding as well as on PDI antimicrobial outcome against an array of ESKAPE pathogens as well as resilient Bacillus cereus endospores. Therefore, binding assays were performed to measure the quantity of porphyrins bound to ESKAPE pathogens. We also assessed the PDI bactericidal efficacy using 405 nm LED for the PdT4 and PdC14 as well as 430 nm LED for the ZnT4 and ZnC14 metalloporphyrin derivatives against selected species of the ESKAPE pathogens and B. cereus endospores. To determine how much of the bactericidal PDI outcome correlates to both bound versus unbound portions of the PdT4 and PdC14, a binding dependence assay was performed. Our findings show an increased bacterial binding whereby 79% and 68% of total PdC14 was detected in Enterococcus faecium and A. baumannii respectively, compared to 0% binding associated with PdT4. Relative to ZnT4, ZnC14 shows binding improvement whereby 49% and 80% binding occurred compared to only 2% and 0% ZnT4 detection in both MRSA and A. baumannii. Overall, both metalloporphyrin show strong PDI bactericidal activity against both Gram-positive and Gram-negative bacteria. PDI against Gram-positive E. faecium resulted in 99.96% reduction using PdC14 at 0.3125 J/cm2 whereas PdT4 showed lower reduction rate at 97.82%. In Gram-negative A. baumannii, 99.88% bacterial reduction rate was achieved using PdC14 at 5 J/cm2 irradiance whereas PdT4 showed 90.97% . ZnC14 shows >99.99% killing rate of A. baumannii whereas ZnT4 only shows 9.74% reduction using 0.25 J/cm2 irradiance. MRSA also showed 9.00E+07 log inactivation (>99.99%) using ZnC14 at 0.25 J/cm2 irradiance. Overall, these data highlight metalloporphyrin improvement as a PS in bacterial binding and PDI antimicrobial activity upon insertion of lipophilic C14 alkyl chain.
Keywords: ESKAPE pathogens; Metalloporphyrin; Photodynamic inactivation; Photosensitizers; Porphyrin